2006
DOI: 10.1002/lt.20745
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative steroids administration on ischemia-reperfusion injury and systemic responses in liver surgery: A prospective randomized study

Abstract: Hepatic injury secondary to warm ischemia-reperfusion (I/R) injury and alterations in haemostatic parameters are often unavoidable events after major hepatic resection. The release of inflammatory mediator is believed to play a significant role in the genesis of these events. It has been suggested that preoperative steroid administration may reduce I/R injury and improve several aspects of the surgical stress response. The aim of this prospective randomized study was to investigate the clinical benefits on I/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
135
5
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 52 publications
9
135
5
3
Order By: Relevance
“…Shimada et al (34) reported that morbidity rates including hyperbilirubinemia, anastomotic leakage, and liver dysfunction in patients with esophagectomy were significantly lower in a steroid group than in a non-steroid group. In addition, the median hospital stay was reported to be shorter in a steroid group, and adverse effects of steroid use, such as abnormality in glucose tolerance and delay in wound healing, did not occur following liver surgery (35). In the present study, the level of urine UTI in the steroid group was decreased compared to that in the non-steroid group (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Shimada et al (34) reported that morbidity rates including hyperbilirubinemia, anastomotic leakage, and liver dysfunction in patients with esophagectomy were significantly lower in a steroid group than in a non-steroid group. In addition, the median hospital stay was reported to be shorter in a steroid group, and adverse effects of steroid use, such as abnormality in glucose tolerance and delay in wound healing, did not occur following liver surgery (35). In the present study, the level of urine UTI in the steroid group was decreased compared to that in the non-steroid group (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…A recent prospective clinical trial assessed the use of preoperative steroid administration on outcome after hepatectomy (108). Patients (n = 36) treated with preoperative methylprednisolone (500 mg) before induction of anesthesia had lower serum transaminases, coagulation parameters, and inflammatory cytokines (TNF-α and IL-6).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…8 It is of great interest that the possible clinical effects of a high pulse dose of steroids include the prevention of bacterial translocation and immunosuppression induced by the operation itself. [9][10] Concerns exist on the clinical use of high-dose steroids, because of the possible side effects and the risk of adrenal suppression. However, no adverse effects have actually been reported in the previous study about high-dose steroids.…”
Section: Effects Of Adjuvant Therapy On the Outcomes Of Surgical Manamentioning
confidence: 99%